Three new species of Lamprigera Motschulsky (Coleoptera, Lampyridae) from China, with notes on known species - Dong, Zhiwei; Yiu, Vor; Liu, Guichun; He, Jinwu; Zhao, Ruoping; Peng, Yanqiong; Li, Xueyan (Zootaxa, 2021)
Lamprigera is found only in those countries from the Himalaya–Karakoran –Tibet region to SE Asia where 17 species have been previously recorded. These 17 include four species from China. In this work, combined molecular data (COI) and morphological traits identified eight species in our collections. Among these, we found three Chinese species (Lamprigera alticola Dong & Li, sp. nov., Lamprigera luquanensis Dong & Li, sp. nov. and Lamprigera magnapronotum Dong & Li, sp. nov.) that are new to science, bringing the total number of species of Lamprigera to 20 (17+3), and four other known species that are herein newly recorded for the first time in China. These four new records, the three new species, and the four previously known records bring the total number of Chinese species to 11. The morphological traits, especially the male genitalia and pronotum, are described for all eight species. We conclude that male genitalia and pronotum are the most important diagnostic traits for separating species of Lamprigera, and this is confirmed by COI data.